Air war over Spain aviators, aircraft and air units of the Nationalist and Republican Air Forces, 1936-1939 - Permuy Lopez, Rafael A. (Allan Pub., 2009)
The air campaigns fought during the Spanish Civil War prompted technical and tactical developments for all parties - from the actual deployment of air power through to communications. This work examines the opposing air forces in the Spanish Civil War as well the intervention of the German, Italian and Soviet air forces in their respective guises.